Ayat-Ayat Tentang Puasa dan Apa-Apa yang Berhubungan Dengannya - Shofiyatun Nafisah Lubis; Imelda Fedian; Airil Ihza Harefa (STIKes Ibnu Sina Ajibarang, 2024)
: Fasting is a practice that involves abstaining from eating, drinking, and certain activities for a certain period of time, often for religious or health purposes. In a religious context, fasting is carried out as a form of devotion and spiritual discipline, as practiced in various religious traditions including Islam, Christianity, Judaism and Hinduism. In Islam, fasting during the month of Ramadan is one of the five pillars of Islam that every eligible Muslim must carry out. Fasting also has widely recognized health benefits, including weight control, increased metabolism, and detoxification of the body. However, fasting must also be done carefully, especially for individuals with certain health conditions, to avoid negative side effects such as dehydration and malnutrition. Scientific studies show that intermittent fasting, an eating pattern that involves alternating periods of fasting with periods of eating, can improve metabolic and cardiovascular health. This abstract explores various aspects of fasting, including anything related to fasting and also verses that discuss fasting. The method used in writing this journal is the library research method.